Odpowiedź :
Odpowiedź:
Zad.4
a) [tex]1\frac{4}{7}+\frac{5}{7}=1\frac{9}{7}=2\frac{2}{7}[/tex]
b) [tex]2\frac{1}{4}+1\frac{2}{5}=2\frac{5}{20}+1\frac{8}{20}=3\frac{13}{20}[/tex]
c) [tex]1\frac{2}{15}-\frac{4}{15}=\frac{17}{15}-\frac{4}{15}=\frac{13}{15}[/tex]
d) [tex]5\frac{3}{5}-2\frac{3}{10}=5\frac{6}{10}-2\frac{3}{10}=3\frac{3}{10}[/tex]
Zad. 5
a) [tex]2\frac{2}{3}+1\frac{4}{5}=2\frac{10}{15}+1\frac{12}{15}=3\frac{24}{15}=4\frac{9}{24}=4\frac{3}{8}[/tex]
b) [tex]3\frac{2}{5}-1\frac{3}{7}=3\frac{14}{35}-1\frac{15}{35}=2\frac{49}{35}-1\frac{15}{35}=1\frac{34}{35}[/tex]
Zad.6
a) [tex]\frac{3}{4}*\frac{1}{7}=\frac{3}{28}[/tex]
b) [tex]\frac{3}{10}*\frac{6}{11}=\frac{9}{55}[/tex]
c) [tex]\frac{4}{15}*\frac{3}{8}=\frac{1}{10}[/tex]
d) [tex]1\frac{3}{5}*\frac{5}{32}=\frac{8}{5}*\frac{5}{32}=\frac{1}{4}[/tex]
Zad.7
a) [tex]\frac{3}{8}:5=\frac{3}{8}*\frac{1}{5}=\frac{3}{40}[/tex]
b) [tex]\frac{9}{14}:6=\frac{9}{14}*\frac{1}{6}=\frac{3}{28}[/tex]
c) [tex]1\frac{4}{9}:13=\frac{13}{9}*\frac{1}{13}=\frac{1}{9}[/tex]
d) [tex]3\frac{1}{5}:4=\frac{16}{5}*\frac{1}{4}=\frac{4}{5}[/tex]
Szczegółowe wyjaśnienie: